First description of l.-mining Nepticulidae and Tischeriidae (Insecta, Lepidoptera) feeding on the Chilean endemic plant genus Podanthus Lag. (Asteraceae) - Cumbicus Torres, N. (2016)
Copyright © 2016 Magnolia Press. Despite taxonomic and conservation interest in the Chilean endemic plant genus Podanthus Lag. (Asteraceae: subfamily Asteroideae, tribe Heliantheae), no Podanthus-feeding Nepticulidae or Tischeriidae have ever been recorded. Here, on the basis of material reared from Podanthus from central Mediterranean Chile, we present the description of Stigmella podan-Thae sp. nov. (Nepticulidae) and a re-description of Astrotischeria chilei Puplesis & Dikus, 2003. Females and host-plant of the latter species were previously unknown. Both treated species are illustrated with numerous photographs of the leaf-mines, adults of both sexes, and male and female genitalia.